Extraction of Starch, Xylose and Glucose from Oil Palm Stem Using Chemical Steeping and Dilute Acid Hydrolysis Methods - Wong, Lih Jiun (2011)
In Malaysia, oil palm industry is the largest biomass producers compared to other types of biomass generated. With the growth of palm oil production in Malaysia, the amount of oil palm stem generated also shows a corresponding increase. The utilization of oil palm stem in plywood production is not so economically sound due to great variations in physical and mechanical properties. As a result, numerous researches and studies on the chemical derivatives of oil palm trunk have been conducted. This study focused on the total extractable amount of starch, xylose and glucose from oil palm stem using chemical steeping method and dilutes acid hydrolysis. The specific objectives were to determine the chemical composition and the effect of chemical steeping variables (steeping temperature and steeping hours) on the starch yield, and acid hydrolysis parameters (particle sizes, acid concentration and reaction time) on glucose and xylose yield. This research also served to investigate the effectiveness of chemical steeping as pre-treatment for dilute acid hydrolysis. Oil Palm stem were used in powder form of 40 mesh size and dried to 5% moisture content for chemical composition tests prior to chemical analysis whilst 20 mesh, 40 mesh and 60 mesh sizes were used for chemical steeping and dilute acid hydrolysis. Chemical analysis was based on TAPPI standard T 203 for determination of its main composition. Low lignin, hemicelluloses and cellulose content were found in this batch of study. Hemicellulose content is the one for the most important factors for xylose production and glucose produced from cellulose from lignocellulosic. Starch in the oil palm stem was extracted by using chemical steeping method. The oil palm stem powder (20, 40 or 60 mesh) was steeped with 0.2% of sodium metabisulphite (Na2S2O5) and 0.5% of lactic acid (C3H6O3) at room temperature (±26˚C), 40˚C and 50˚C for 36, 48 hours respectively. The result showed that higher starch yield was obtained when steeped with temperature. The optimum starch yield can be obtained by chemical steeping method under 50˚C for 48 hours. Two treatments were employed for dilute acid hydrolysis in producing xylose and glucose from oil palm stem which were carried out 1) without pre-treatment 2) with pre-treatment. The chemical steeping method was treated as a pre-treatment, which the optimum variable from steeping was chosen as the pre-treatment variable (50˚C and 48 hours) for dilute acid hydrolysis. Each of the treatments was treated with three different sulfuric acid concentrations (2%, 4% and 6%) at two different reaction time (30 minutes and 60 minutes) at temperature 115˚C. Analysis of variance revealed statistically significant difference in dilute acid hydrolysis variables for xylose and glucose yield. Significant interaction among the variables was observed for glucose yield, whereas no significant interaction for the dilute acid hydrolysis variable was observed for xylose. For xylose, individual variables were affecting the xylose yield independently. The Tukey test showed the highest glucose yield, which is 25.5% (dry w/w) was obtained using the dilute acid hydrolysis with parameter of 2% sulfuric acid concentration reacted for 30 minutes on 60 meshes without pre-treated oil palm stem powder. On the other hand, the presence of pre-treatment before dilute acid hydrolysis process contributed to higher xylose yield (35.0%) from oil palm stem. The particle sizes of oil palm stem powder (20 mesh, 40 mesh dan saiz 60 mesh) and acid concentration (2%, 4% dan 6%) were not significant different for xylose yield but higher xylose yield can be extracted with the presence of pre-treament and hydrolysis for 60 minutes. Conclusively, the oil palm stem has substantial amount of starch, xylose and glucose. Starch was effectively extracted from oil palm stem using chemical steeping method. The presence of chemical steeping as pre-treatment was the most independent variable in affecting the optimum glucose and xylose yield extracted from oil palm stem.